4(v-7)+8(8+7v)=36

Simple and best practice solution for 4(v-7)+8(8+7v)=36 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(v-7)+8(8+7v)=36 equation:


Simplifying
4(v + -7) + 8(8 + 7v) = 36

Reorder the terms:
4(-7 + v) + 8(8 + 7v) = 36
(-7 * 4 + v * 4) + 8(8 + 7v) = 36
(-28 + 4v) + 8(8 + 7v) = 36
-28 + 4v + (8 * 8 + 7v * 8) = 36
-28 + 4v + (64 + 56v) = 36

Reorder the terms:
-28 + 64 + 4v + 56v = 36

Combine like terms: -28 + 64 = 36
36 + 4v + 56v = 36

Combine like terms: 4v + 56v = 60v
36 + 60v = 36

Add '-36' to each side of the equation.
36 + -36 + 60v = 36 + -36

Combine like terms: 36 + -36 = 0
0 + 60v = 36 + -36
60v = 36 + -36

Combine like terms: 36 + -36 = 0
60v = 0

Solving
60v = 0

Solving for variable 'v'.

Move all terms containing v to the left, all other terms to the right.

Divide each side by '60'.
v = 0.0

Simplifying
v = 0.0

See similar equations:

| 3x-7+2-5x=15 | | 16.66d+.66=.25d-.50 | | 48=7x+2x+3 | | p+17=-9 | | 8=17-a | | -5x+10=-10 | | -20g+7(3h+3g)-14h=0 | | 8x=41-(1-3x) | | 2(1x+10)=10 | | c=.90c | | (7y-6)-(3y+8)= | | 5x-3-4x=-12 | | 2x-4(x-4)=-5+4x-9 | | 4(b-2)=12 | | 129.19=2.25h+71.19 | | -5[(3x+1)-(4x-2)]=6(6-x)-4 | | 6(1-6x)+5(-x-8)= | | 9y-29=-69+4y | | (1+w)(5w+7)=0 | | 10m+7=27 | | 6(3-2x)=30 | | 7s-10=2+s | | 4m-4=16 | | 7(y+3)=9y+23 | | 5x-10=275 | | 10+2(-4)= | | X^6+19x=216 | | -5(4x+7)=185 | | 4x^2-15=4x | | 3x+35=2x+205 | | 4x+5+3x+8=90 | | 0.80x+.05(20-x)=.10(-80) |

Equations solver categories